Pengaruh Kredibilitas Endorser dan Kesesuaian Endorser dengan Produk pada Citra Merek (studi pada iklan produk BB cream Pondâs dengan endorser Sandra Dewi) - , ALFIAN ZAKKI, Sudiyanti, S.E., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of the study is analyze the influence of endorserâs credibility (attractiveness, trustworthiness, and expertise) and endorser match-up product on brand image of a cosmetic product, which is BB cream Pondâs ads that was endorsed by Sandra Dewi. The primary data were collected directly by distributing questionnaires to 150 females. The sampling method use convenience technique and the linear multiple regression was applied. The results demonstrated all hypotheses have been confirmed. The conclusion that can be drawn from the research are endorserâs credibility (attractiveness, trustworthiness, and expertise) and endorser match-up product have significant positive effect on brand image.